Optimalisasi Pelayanan Administrasi Di Bagian Operasional Satuan Brimob Kepolisian Daerah Kalimantan Tengah (Soetomo Magister Ilmu Administrasi, 2023)
The demand to always strengthen the police administration system, especially the police administration system in the Central Kalimantan Regional Police Brimob Unit, which is felt to have not run as expected, while changes in environmental factors are very fast in society and need to be anticipated by the ranks of the Central Kalimantan Regional Police Brimob Unit so that the kamtibmas situation remains under control. Furthermore, in this study, the research problem was formulated How is the optimization of administrative services in the operational section of the Central Kalimantan Regional Police Brimob Unit What are the factors that affect the quality of administrative services in the operational section of the Central Kalimantan regional police brimob unit The objectives of this study include: to identify the optimization of administrative services in the operational section of the Central Kalimantan regional police brimob unit and to find out the factors that affect the quality of administrative services in the operational section. The type of research used in this research is a qualitative approach. The results of this study that to optimize administrative services in the operational section of the Central Kalimantan regional police brigade unit, it is necessary to 1. Implement an administrative information system, 2. Simplify administrative procedures, 3. Administrative skills training, 4. Increased collaboration between teams, 5. Utilization of technology and 6. Monitoring and evaluation The factors that affect the quality of administration in the operational section are employee competence, administrative systems and procedures, infrastructure and technology, internal coordination, organizational culture, service user satisfaction, and monitoring and evaluation. From the results of this study it can be concluded that there is a need to improve administrative services in the operational section of the Central Kalimantan regional police brigade unit. This optimization effort aims to ensure the efficiency and effectiveness of administrative processes related to operational tasks. Keywords: Optimization, Administrative services, Operational department